Pencegahan Bahaya Korupsi Di Indonesia Melalui Pendidikan Anti Korupsi - Ni Komang Ayu Riska Pebrila (Ganesha Civic Education Journal, 2022)
Corruption is a problem that is still being faced today and has become a chronic problem. There fore it is important to know the importance of anti-corruption education. Anti-corruption education is a pillar which is one of the efforts in eradicating corruption in Indonesia which still prioritizes the role of the community to fight acts of corruption, namely by carrying out supervision, supervision carried out by the community will help the government in succeeding in eradicating corruption. Hence the importance of anti-corruption education because it is known that community participation is very helpful in eradicating corruption. Implementing anti-corruption education, by implementing education it is hoped that students will know more about the dangers of corruption for the survival of the Indonesian people. In the efforts made, it is hoped that the goals of the Indonesian state will be realized, namely the achievement of a just and prosperous society.